BENTUK PENYAJIAN ANSAMBEL GONDANG SABANGUNAN PADA UPACARA PANANGKOK SARING-SARING DI DESA PATOR JANJI MATOGU KECAMATAN ULUAN KABUPATEN TOBA SAMOSIR - Fenny Hannatasya Purba (Grenek: Jurnal Seni Musik, 2018)
The results showed that the presence of Gondang Sabangunan in the village PartorJanji Matogu important role in any traditional events in the village Partor Janji Matoguwhich can be seen from the function, especially in traditional events Panangkok Saringsaring to accompany tortor when dropping crates to the location of the tomb new,accompany tortor the hula when handing rudang-rudang and accompany tortor bonahasuhutan that will bring rudang-rudang into the house. Forms of presentationgondang played using ensemble gondang Sabangunan, this ensemble plays a repertoiregondang sipitu in the event panangkok Saring-saring is Gondang At first, Gondangsomba-somba, Gondang mangaliat, Gondang Pasu-pasu, Gondang sahata saoloan,Gondang hasahaton, Gondang sitiotio , Gondang Sipitu particular musical formgondang mangaliat accentuate the melody played by Bolon sarune musical instrumentsand other musical instruments taganing, ogung, hesek serves as an accompanimentmelody and tempo beats with a value thatisdifferent foreach instrument